HUBUNGAN INTENSITAS MEMBACA CERPEN FIKSI PENGGEMAR DENGAN PEMAHAMAN MAJAS PERBANDINGAN PADA KOMUNITAS NCTZEN MAKASSAR: The Relationship between the Intensity of Reading Short Fiction Stories by Fans and the Understanding of Comparative Figures of Speech in the NCTZEN Community in Makassar - Putri Ramadhani; Mayong; Aswati Asri (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
This study aims to demonstrate the relationship between the intensity of reading fan fiction short stories and the understanding of figures of speech within the NCTZEN community in Makassar. This is an ex post facto quantitative study. It utilised questionnaire distribution and testing techniques. The results indicate that the intensity of reading fan fiction short stories falls into the moderate category, whilst the level of understanding of figurative language falls into the high category. The data was found to be normally distributed following data transformation, with the p-value exceeding the significance level of 0.05 at 0.200. Furthermore, the linearity test result showed 0.119, which exceeded 0.05, and the product-moment correlation test result showed that the calculated r was greater than the table r, namely 0.697 > 0.266. Engaging in reading activities consistently over a long period of time has a positive impact on readers’ comprehension